A mercadoria cultural - Bolognesi, Mario Fernando [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Filosofia, 1996)
Adorno e Horkheimer adotaram a noção de fetichismo da mercadoria para a análise da arte e da cultura. Bens materiais e físicos não são idênticos aos simbólicos. Apesar de dominante, a indústria cultural não pode ser tomada como protótipo de toda análise da cultura. Não se pode reduzir toda a produção cultural da época da economia de mercado a produtos de mercado. A pluralidade de práticas artísticas e culturais, à qual se assiste em países como o Brasil, torna problemático o uso indiscriminado do referencial frankfurtiano.

Adorno and Horkheimer adoted the notion of the fetishism of commodities for the analysis of art and culture. Material, physical goods are not identical to symbolic ones. In spite of being predominant cultural industry can not be taken as the prototype of all analyses of culture. One can not reduce all cultural productives of the period of market economy to market products. The plurality of artistic and cultural practices present in countries like Brazil, does make questionable the indiscriminate use of the Frankfurtian framework.
The cultural commodity
Keywords: Mercadoria; fetichismo; indústria cultural; bens culturais; Commodity; fetishism; cultural industry; cultural goods